2021
DOI: 10.1038/s41467-021-22285-y
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of supramolecular membrane protein–lipid bilayer assemblies through immobilization in a crystalline exoskeleton

Abstract: Artificial native-like lipid bilayer systems constructed from phospholipids assembling into unilamellar liposomes allow the reconstitution of detergent-solubilized transmembrane proteins into supramolecular lipid-protein assemblies called proteoliposomes, which mimic cellular membranes. Stabilization of these complexes remains challenging because of their chemical composition, the hydrophobicity and structural instability of membrane proteins, and the lability of interactions between protein, detergent, and li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 58 publications
1
45
0
Order By: Relevance
“…A challenge in whole-cell vaccine formulation is inactivating the bacteria with minimal damage to the surface epitopes, including delicate membrane-bound proteins and complex oligosaccharides. Biomimetic mineralization with ZIF is extremely gentle, and we have previously shown that membrane bound proteins are not only preserved but protected by ZIF encapsulation in lipid nanoparticles . To show that our ZIF encapsulation approach preserves natively folded proteins better than traditional methods of inactivation, we conducted an agglutination assay using yeast.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A challenge in whole-cell vaccine formulation is inactivating the bacteria with minimal damage to the surface epitopes, including delicate membrane-bound proteins and complex oligosaccharides. Biomimetic mineralization with ZIF is extremely gentle, and we have previously shown that membrane bound proteins are not only preserved but protected by ZIF encapsulation in lipid nanoparticles . To show that our ZIF encapsulation approach preserves natively folded proteins better than traditional methods of inactivation, we conducted an agglutination assay using yeast.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To address this challenge, we developed a biomimetic encapsulation , methods that fully encase individual bacteria inside a crystalline polymeric matrix called Z eolitic I midazolate Frameworks (ZIFs  Scheme ). We and others showed that mixing an array of biological molecules, including fluorescent proteins, insulin, proteins, , IgG, viral nanoparticles, ,, RNA, yeast, , proteoliposomes, and Gram-positive and -negative bacteria within the ZIFs framework, incarcerates the target in a biodegradable matrix. ZIFs are a subclass of a broader family of solid-state single crystal metal organic frameworks (MOFs) characterized by interconnected organic ligands linked by metal nodes extending infinitely in all directions (Scheme A and B).…”
Section: Introductionmentioning
confidence: 99%
“…This required cooling/cold-chain makes the delivery of vaccines expensive, and the cost of keeping them cold can account for as much as 80% of the total cost of the immunization (Ashok, Brison, & LeTallec, 2017;Bogataj, Bogataj, & Vodopivec, 2005;Karishma, Donna, Timothy, & Neena, 2012;Setia et al, 2002;Welch et al, 2018). This instability has made controlled release strategies for delivery of LNP-based vaccines difficult, though emerging approaches using metal-organic frameworks have shown considerable promise (Herbert et al, 2021). The ideal 21st-century vaccine should be safe, patient-friendly, and stable enough such that it can be stored at ambient conditions and provide long-term immunity after one administration.…”
Section: The Interplay Between the Realities Of The Immune System And Vaccine Technologymentioning
confidence: 99%
“…Copyright 2016 John Wiley and Sons) interesting because they showed a more stable method to encapsulate antigens and demonstrated that the biomaterial could prime the immune system without the need of the adjuvant. A more recent development has shown that biomimetic coating of ZIFs on lipid nanoformulations promote their stability for many months in the mail (Herbert et al, 2021). This could have potential applications for stabilizing the newest lipid-based vaccines.…”
Section: Othersmentioning
confidence: 99%
“…Thus, new adjuvants that synergize with mRNA vaccines may be very important in increasing vaccine efficacy, affordability, and stability. Currently, lipid-based delivery systems are used in mRNA vaccines because they demonstrate high transfection efficiency; however, they also require specialized storage to remain stable and lack inherent adjuvant activity [ 115 , 116 ]. New nanoparticle adjuvants show promise in improving mRNA vaccine safety, efficacy, stability, and cost [ 117 , 118 ].…”
Section: Emerging Adjuvant Platformsmentioning
confidence: 99%